Integration of nuclear and mitochondrial gene sequences and morphology reveals unexpected diversity in the forest cobra (Naja melanoleuca) species complex in Central and West Africa (Serpentes: Elapidae) - Wüster, Wolfgang; Chirio, Laurent; Trape, Jean-François; Ineich, Ivan; Jackson, Kate; Greenbaum, Eli; Barron, Cesar; Kusamba, Chifundera; Nagy, Zoltán T.; Storey, Richard; Hall, Cara; Wüster, Catharine E.; et al. (Zootaxa, 2018)
Cobras are among the most widely known venomous snakes, and yet their taxonomy remains incompletely understood, particularly in Africa. Here, we use a combination of mitochondrial and nuclear gene sequences and morphological data to diagnose species limits within the African forest cobra, Naja (Boulengerina) melanoleuca. Mitochondrial DNA sequences reveal deep divergences within this taxon. Congruent patterns of variation in mtDNA, nuclear genes and morphology support the recognition of five separate species, confirming the species status of N. subfulva and N. peroescobari, and revealing two previously unnamed West African species, which are described as new: Naja (Boulengerina) guineensis sp. nov. Broadley, Trape, Chirio, Ineich & Wüster, from the Upper Guinea forest of West Africa, and Naja (Boulengerina) savannula sp. nov. Broadley, Trape, Chirio & Wüster, a banded form from the savanna-forest mosaic of the Guinea and Sudanian savannas of West Africa. The discovery of cryptic diversity in this iconic group highlights our limited understanding of tropical African biodiversity, hindering our ability to conserve it effectively.